The Impact of Artificial Barriers on the Varuna litterata Migration Route in the Lower Serayu River, Central Java and Its Molecular Identification - Sinaga, Sorbakti; Maimunah, Yunita; Ekawati, Arning Wilujeng; Widodo, Maheno Sri (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2024)
The Serayu River is one of the longest rivers in Central Java. Dams built in the lower reaches of the Serayu River are thought to block the migration paths of fish and aquatic macrocrustaceans. This study aimed to determine the effect of dam on Varuna litterata migration and its molecular identification. This research was conducted using the observation method. Migration observations were made on vertical paths while molecular identification of V. litterata in the lower reaches of the Serayu River was compared with existing data in GenBank. The study covered the freshwater area above the Serayu Dam, the open area with freshwater below the Serayu Dam, and the open area with brackish water at the estuary of the Serayu River, with a study length of 33.37 km. The results showed that the presence of dams in the lower reaches of the Serayu River inhibited the migration pattern of V. litterata. The vertical shape of the dam causes only a few V. litterata to migrate to the top of the dam. The dam in the lower reaches of the Serayu River resulted in not many V. litterata being able to migrate to the top of the dam, so there were very few V. litterata found in the population upstream of the dam (115 ind). The results of molecular identification of V. litratata using the cytochrome C oxidase subunit I (COI) gene show that this crab is 100% the same as the data in GenBank and is closely related to Varuna yui and other Varunidae crab species.Keywords: Dams, Molecular, Migration, Serayu River, Varuna litterata